Model Integratif Logoterapi dan Psikoterapi Islam: Rekonstruksi Will to Meaning sebagai Will to Worship and Serve Allah - Imam Zulkhairi; Khairunnas Rajab (Socius: Jurnal Penelitian Ilmu-Ilmu Sosial, 2026)
The phenomenon of a crisis of meaning in life has become an increasingly prominent psychological issue in modern society, marked by rising existential emptiness, depression, and hopelessness. Viktor E. Frankl, through logotherapy, emphasized that the primary human motivation is the will to meaning, namely the fundamental drive to find meaning in life. This article aims to analyze the concept of the will to meaning within logotherapy and reconstruct it from the perspective of Islamic psychotherapy. The study employs a literature review method by examining relevant books and scholarly journal articles on logotherapy, meaning in life, and Islamic psychology. The findings reveal points of convergence between logotherapy and Islam in their recognition of the spiritual (noetic) dimension, the freedom to choose one’s attitude, and the possibility of finding meaning in suffering. However, a fundamental difference lies in the source of meaning: logotherapy is existential and individual in nature, whereas Islam is grounded in divine revelation and tawhid, with the ultimate orientation toward seeking Allah’s pleasure. Within the Islamic framework, the concept of the will to meaning is reconstructed as the will to worship and serve Allah, where the highest meaning is devotion and submission to Him. Practically, logotherapeutic techniques such as dereflection, paradoxical intention, and Socratic dialogue can be integrated with the concepts of tazkiyatun nafs, tawakal, and muhasabah in Islamic counseling. This integration produces a psychotherapeutic model that is not only clinically effective in enhancing resilience and mental health, but also theologically authentic for Muslim clients. Thus, the synthesis of logotherapy and Islamic teachings contributes to strengthening a contemporary Islamic psychotherapy framework grounded in meaning and tawhid.